The quest for world order and human dignity in the twenty-first century : constitutive process and individual commitment : general course on public international law - Reisman, W. Michael (William Michael), 1939- (Pocketbooks of the Hague Academy of International Law., 2013)
This General Course is concerned, first, with understanding and assessing the aggregate performance of the world constitutive process, in present and projected constructs; second, with providing the intellectual tools that can enable those involved in making decisions to be more effective, whether they are operating in islands or offshore; and, third, with inquiring into ways the international legal system might be improved. Reisman identifies the individual as the ultimate actor in international law and explores the dilemmas of meaningful individual commitment to a world order of human dignit.